PERAN ORANG TUA DAN GURU DALAM MEMBENTUK MINAT SISWA TERHADAP EKSTRAKURIKULER TAPAK SUCI DI SMK MUHAMMADIYAH 3 SUKOLILO KABUPATEN PATI - Fachrudin, Dedi; Gatot Jariono; Nurhidayat Nurhidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted to determine the role of parents and teachers in forming students' interest in Tapak Suci extracurricular activities at SMK Muhammadiyah 3 Sukolilo, Pati District. Benefits of this research: 1. Can enrich literature regarding the role of parents and teachers in character education, especially in forming students' interest in extracurricular activities, 2. Provide insight for parents, teachers and schools in understanding the importance of their role in forming students' interest in extracurricular activities. This research uses a quantitative descriptive approach with survey methods. The results of the research show that the role of parents and teachers is in shaping students' interest in Tapak Suci extracurricular activities at SMK Muhammadiyah 3 Sukolilo, Pati District. Research results from 43 respondents showed that 80% strongly agreed and agreed with parental support, 67% strongly agreed and agreed with teacher support, 75% were very interested and interested in student interests. From the results of these respondents, it can be concluded that the support of parents and teachers has a significant influence on increasing students' interest in participating in the Tapak Suci extracurricular at SMK Muhammadiyah 3 Sukolilo, Pati District.